Do the intercropping with Crotalaria spectabilis and Urochloa ruziziensis reduce the maize agronomic performance? - Souza, Stefany Silva de [UNESP]; Couto Junior, Pedro Afonso [UNESP]; Flores, Jordana de Araujo [UNESP]; Coellio, Anderson Prates [UNESP]; Lemos, Leandro Borges [UNESP] (Univ Federal Goias, 2022)
Depending on the climate and soil conditions and management, the intercropping of maize with soil cover plants may reduce the cereal agronomic performance. This study aimed to assess the effects of intercropping with Urochloa ruziziensis and Crotalaria spectabilis on the maize agronomic performance and the straw production and quality after the harvest. Three treatments (single maize and maize intercropped with U. ruziziensis and with C. spectabilis) were distributed into a randomized blocks design. The growth and production components and the maize grain yield were evaluated in the three systems, as well as the straw production and nitrogen accumulation in each system. The intercropping systems did not decrease the maize yield and agronomic performance, if compared to the single crop, regardless of the evaluated species. The intercropping with C. spectabilis and U. ruziziensis presented a straw production 24 and 11 % higher, respectively, and the intercropping with C. spectabilis resulted in a straw nitrogen accumulation 39 % higher, when compared to the single maize crop.
Keywords: Zea mays L.; soil cover plants; straw production; no-tillage system